The covariance biplot and stock market data: An alternative relative strength chart - G. D.I. Barr; J. F. Affleck-Graves (South African Journal of Business Management, 1987)
Relative strength analysis is an important technique for many investment analysts. In this paper an alternative to the traditional relative strength chart is proposed, based on the covariance biplot. It is argued that this method provides more information than the traditional relative strength analysis in that it provides a visual picture of both the relative riskiness of the individual securities and the degree of co-movement between the various securities, in addition to the change in relative strength over a number of time periods. A methodology is proposed for transforming stock-market data into a form suitable for the covariance biplot routine. This transformation involves both a smoothing and scaling of the original price series data. The methodology is illustrated by application to six of the JSE Actuarial Sector Indices and a step-by-step guide to the interpretation of the covariance biplot is provided.
Keywords: 650